The Effect of Human Resource Experience on the Quality of SKPD Financial Statements with the Government's Internal Control System as a Moderating Variable - Rosnawaty, Rini; Silviana, Silviana (Journal of Management and Administration Provision, 2024)
The purpose of this study is to test the influence of human resource experience on the quality of SKPD financial statements with the government's internal control system as a moderating variable. This type of research uses explantory with the use of a quantitative approach. The population in this study is 38 Regional Apparatus Work Units (SKPD) that have general functional positions in the preparation of financial statements in the West Java Provincial Government. The method of determining the sample is the census method so that the entire population is used as a research sample. The data in this study are primary data and data collection techniques using questionnaires. Hypothesis testing uses the Moderation Regression Model with the help of the Statistical Product and Service Solution (SPSS) version 25 program. The results of this study prove that human resource experience has a positive and insignificant influence on the quality of SKPD financial statements, and the government's internal control system is unable to increase the influence of human resource experience on the quality of SKPD financial statements. It is hoped that there will be improvements in government apparatus, as well as leaders to always provide support and evaluation of employees and experience in creating a supportive work environment to improve the quality of SKPD financial reports through education and training.